Lifting and stabilizing of two-wheeled wheelchair system using interval type-2 fuzzy logic control based spiral dynamic algorithm - N. A. A. Razali; Nor Maniha Abdul Ghani; Bifta Sama Bari (Institute of Advanced Engineering and Science, 2021)
The current study emphasizes on improving an interval type-2 fuzzy logic control (IT2FLC) system through the use of spiral dynamics algorithm (SDA) optimization in stabilizing a transformational two-wheeled wheelchair. The main contribution of this research is to reduce vibrations while performing the lifting and stabilization of a wheelchair from its standard four-wheeled to two-wheeled transformation. IT2FLC based SDA was used to enhance the system’s stability performance by obtaining the optimized value for input and output controller gains and IT2FLC parameters for IT2FLC. System modeling was done through development within the SimWise 4D software environment, which was then integrated with MATLAB/SIMULINK for control purposes. The proposed algorithm has demonstrated improved tilt angle performance with reduced noise and lower torque when various disturbances were applied, as compared to a system solely controlled by IT2FLC without any optimization. Moreover, the proposed algorithm has also comprehensively outperformed previous controllers in terms of system’s stability, further demonstrated its superiority as a system controller within transformational wheelchairs.